Good Regulatory Governance Sebagai Wujud Akuntabilitas Pelayanan Publik - Leo Agustino (Centre for Public Policy and Management Studies, 2003)
Autonomy, at the moment, misinterpreted as auto-money; is providing money as much as possible for the local autonomy government. Therefore, since UU No. 22 tahun 1999 is implemented, a lot of local regulation problems has emerged, especially entail to local taxes and local retributions that may distort economic activities. Some cases in West Java Province, Kota Bandung, Kabupaten Garut, Kabupaten Ciamis, and also Kabupaten Cirebon showed the problem. To prevent the appearance of local regulations problem, experiences in some state, such as : United States of America, Australian, English, Denmark, Dutch, and Japan, they run a cheerful concept Regulatory Impact Assessment (RIA), as a representation of Good Regulatory Governance. There are four matters which are need to be paid attention in policy formulation –especially entail to local taxes and retributions– namely: The Principle of Competitive Neutrality, The Principle of Minimum Effective Regulations, The Principle of Transparency Participation and The Principle of Costs-Benefits Effectiveness.